1992
DOI: 10.1523/jneurosci.12-06-02381.1992
|View full text |Cite
|
Sign up to set email alerts
|

Retinal growth in foveated teleosts: nasotemporal asymmetry keeps the fovea in temporal retina

Abstract: Fish retinas continue to grow throughout life by adding neurons at the margin, with the result that cells born at a peripheral site are steadily displaced toward the center of the enlarging retina. This presents a functional problem for fish with specialized temporal areas such as a fovea--how to reconcile continual growth with the maintenance of a temporal location for the fovea. One possibility is that the retina grows asymmetrically, with most new retina added nasally, relatively little temporally. I have t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
7

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 19 publications
2
54
0
7
Order By: Relevance
“…The resulting eye cups were fixed by immersion in 4% paraformaldehyde in 0.05 M PO, buffer overnight. One or more small pellets of the fluorescent carbocyanine dye DiI (l,l'-dioctadecyl-3,3,3',3'-tetramethylindocarbocyanine perchlorate;Molecular Probes, Eugene, OR;Honig and Hume, 1986;Godement et al, 1987) were embedded within the cut face of the optic nerve (n = 13), and the eye cups were incubated in fixative at 45°C for 5 d. DiI was incoruorated into retinal aanelion cell (RGC) axonal membranes local to the pellet, and retrogGde?y labeled annuli of RGC somata and dendrites (Easter, 1992;Cameron and Easter, 1993), and one of these annuli generally intersected the lesion site or lay peripheral to it. Retinal whole-mounts were made with the pigment epithelium side down, cover slipped with 50% glycerol, 50% PO, buffer, and viewed with epifluorescence microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting eye cups were fixed by immersion in 4% paraformaldehyde in 0.05 M PO, buffer overnight. One or more small pellets of the fluorescent carbocyanine dye DiI (l,l'-dioctadecyl-3,3,3',3'-tetramethylindocarbocyanine perchlorate;Molecular Probes, Eugene, OR;Honig and Hume, 1986;Godement et al, 1987) were embedded within the cut face of the optic nerve (n = 13), and the eye cups were incubated in fixative at 45°C for 5 d. DiI was incoruorated into retinal aanelion cell (RGC) axonal membranes local to the pellet, and retrogGde?y labeled annuli of RGC somata and dendrites (Easter, 1992;Cameron and Easter, 1993), and one of these annuli generally intersected the lesion site or lay peripheral to it. Retinal whole-mounts were made with the pigment epithelium side down, cover slipped with 50% glycerol, 50% PO, buffer, and viewed with epifluorescence microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, PCNA-positive cells were located at the extreme margin of all retinas (Fig. 1 A), corresponding to the location of the CGZ (Johns, 1977;Easter, 1992;Cameron 1995). BrdU incorporation was also observed in this location (Fig.…”
Section: Growth and Structure Of Cellular Patterns In Normal Retinamentioning
confidence: 75%
“…Studies have shown that animate vision has much higher resolution in the center of the visual field than in the periphery [9], [13], [14], [16], [20], [21], [23], [31], [32]. Several mathematical models and vision systems have been developed based on this variable resolution concept [4], [6], [24], [26], [28], [33].…”
Section: The Vr Transformmentioning
confidence: 99%
“…We can define an iteration step which will converge to the zero crossing (16) Now, for every angle relative to a fovea we have to provide and , and use the iteration procedure to numerically compute and .…”
Section: Varying Distortion and Scaling Factors For Optimal Effectmentioning
confidence: 99%